2008
DOI: 10.1002/prot.22304
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of formation of the C‐terminal β‐hairpin of the B3 domain of the immunoglobulin binding protein G from Streptococcus. I. Importance of hydrophobic interactions in stabilization of β‐hairpin structure

Abstract: We previously studied a 16-amino acid-residue fragment of the C-terminal β-hairpin (residues 46-61), ], of the B3 domain of the immunoglobulin binding protein G from Streptoccocus, and found that hydrophobic interactions and the turn region play an important role in stabilizing the structure. Based on these results, we carried out systematic structural studies of peptides derived from the sequence of IG(46-61) by systematically shortening the peptide by one residue at a time from both the C and the N terminus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
52
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(68 citation statements)
references
References 76 publications
12
52
4
Order By: Relevance
“…Using this approach, as the backbone H-bond interactions were defined solely as enthalpic constraints, our results show that backbone H-bonds only have a minor effect on the sigmoidal behavior (cooperative behavior) because of their small free energy contribution. This result is consistent with Scheraga and his coworkers, who pointed out that no clear evidence supports the presence of backbone H-bonds in non-turn regions [8,66,67,[80][81][82][83][84]. In other words, the backbone H-bond interaction may not contribute as much as expected in the cooperative formation of β-hairpins but may play only a structural as well as energetic constraint in modulation of the cooperative system [see Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Using this approach, as the backbone H-bond interactions were defined solely as enthalpic constraints, our results show that backbone H-bonds only have a minor effect on the sigmoidal behavior (cooperative behavior) because of their small free energy contribution. This result is consistent with Scheraga and his coworkers, who pointed out that no clear evidence supports the presence of backbone H-bonds in non-turn regions [8,66,67,[80][81][82][83][84]. In other words, the backbone H-bond interaction may not contribute as much as expected in the cooperative formation of β-hairpins but may play only a structural as well as energetic constraint in modulation of the cooperative system [see Fig.…”
Section: Discussionsupporting
confidence: 89%
“…We found that, even for peptides of different length, which share a common 6-residue fragment, the following conformational properties remain unchanged: (i) we found that the 6-residue sequence corresponding to the turn region in the structure of the β-hairpin always possesses a structure very similar to that observed in the structure of the native protein, regardless of the peptide length used in our study. Moreover, we performed our study over a relatively wide range of temperatures (283 - 323 K), and found that the conformational properties of the turn region are not temperature dependent;22,33-35 (ii) our previous study22,33-35 also showed that, regardless of the peptide length, the general shape of the investigated peptide resembles a β-hairpin-like structure, which is stabilized by long-range hydrophobic interactions between nonpolar residues. We did not find any evidence that hydrogen bonds participate in the structure stabilization (some hydrogen bonds are observed within the turn region, but they have only very local character) as was suggested in earlier studies 32…”
Section: Introductionmentioning
confidence: 76%
“…As in our previous studies22,33-35 we used the DSC method to determine thermal stability41 and possible tendency to aggregation of the peptide 42. The DSC experiment can detect oligomerization/aggregation processes in a wide range of temperatures, using a very small amount of an investigated compound, and can show if the process of aggregation/oligomerization is reversible with changes of temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The b-hairpin from the FBP28 protein is known to initiate the folding of this protein [8]. This is an independently forming region whose folding is not induced by a b-hairpin and is consequently an excellent object by which to study the factors that influence b-hairpin formation.…”
Section: Introductionmentioning
confidence: 99%